Hospital Bed for Diabetes Care: An Invention to Support Professional and Hygienic Nursing Practice - Sodiq Kamal; Suroto Munahar; Aries Abbas; Yoshifumi Ito; Agus Wahyudi (Mechanical Engineering for Society and Industry, 2021)
Appropriate diabetes mellitus (DM) wound care requires safe and comfortable space and facilities for patients and nurses. However, the existing hospital bed for DM has not supported the safety and comfort for nurses to serve patients, including the problem of liquid waste and some DM wounds emit a foul smell. Therefore, a hospital bed for DM wound care was designed in this research to support professional, efficient, ergonomic, and safe nursing practice. Multidisciplinary collaboration by engineers, wound nursing practitioners, and industry is carried out in this project. The level of risk of work disturbances was evaluated using a rapid entire body assessment (REBA), the level of risk of contamination was evaluated by a qualitative exposure assessment, and the level of comfort was measured using the visual analog method. Trials on 30 respondents consisting of 28 nurses and 2 doctors indicated that they were comfortable working with the new design of this prototype with lower risk.